2021
DOI: 10.1136/jitc-2020-002259
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF as a suitable alternative to GM-CSF to boost dinutuximab-mediated neutrophil cytotoxicity in neuroblastoma treatment

Abstract: BackgroundCurrent immunotherapy for patients with high-risk neuroblastoma involves the therapeutic antibody dinutuximab that targets GD2, a ganglioside expressed on the majority of neuroblastoma tumors. Opsonized tumor cells are killed through antibody-dependent cellular cytotoxicity (ADCC), a process mediated by various immune cells, including neutrophils. The capacity of neutrophils to kill dinutuximab-opsonized tumor cells can be further enhanced by granulocyte-macrophage colony-stimulating factor (GM-CSF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…Furthermore, the overall clinical response of neuroblastoma patients has been found to be further improved by the addition of granulocyte-macrophage colony-stimulating factor (GM-CSF), acting on myeloid cells including neutrophils, to the anti-GD2 treatment regime [ 14 , 21 , 22 , 23 , 24 ]. Overall, from the above-mentioned studies and a variety of others, it has further become apparent that neutrophils can be stimulated by cytokines such as GM-CSF or granulocyte colony-stimulating factor (G-CSF), given either alone or in combination with interferon-gamma (IFNγ), in order to improve their in vitro IgG-mediated cytotoxicity [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the overall clinical response of neuroblastoma patients has been found to be further improved by the addition of granulocyte-macrophage colony-stimulating factor (GM-CSF), acting on myeloid cells including neutrophils, to the anti-GD2 treatment regime [ 14 , 21 , 22 , 23 , 24 ]. Overall, from the above-mentioned studies and a variety of others, it has further become apparent that neutrophils can be stimulated by cytokines such as GM-CSF or granulocyte colony-stimulating factor (G-CSF), given either alone or in combination with interferon-gamma (IFNγ), in order to improve their in vitro IgG-mediated cytotoxicity [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that G-CSF may not be an appropriate agent for patients with high-risk neuroblastoma, as neuroblastoma cell lines express mRNA for the G-CSF receptor and are stimulated in response to exogenous G-CSF, leading to a more aggressive biologic behavior and increased invasiveness. Martinez Sanz et al 1 reported in vitro G-CSF did not show increased neuroblastoma cell growth or a change in the susceptibility of neuroblastoma to neutrophil-mediated cytotoxicity as compared with the control, and no evidence of effect on the neuroblastoma phenotype.…”
mentioning
confidence: 96%
“…We read with great interest the work by Martinez Sanz et al 1 ‘G-CSF as a suitable alternative to GM-CSF to boost dinutuximab-mediated neutrophil cytotoxicity in neuroblastoma treatment,’ published in the Journal for ImmunoTherapy of Cancer on May 28, 2021. The authors note access to recombinant human granulocyte-macrophage colony-stimulating factor (rhu GM-CSF; sargramostim (yeast-derived)) is limited outside of North America, potentially leading to suboptimal treatment of patients with neuroblastoma and therefore necessitating an alternative agent to stimulate dinutuximab immunotherapy-responsiveness in the treatment of neuroblastoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the interest of Dr Mora and Dr Chantada 1 in our recently published work proposing granulocyte colony-stimulating factor (G-CSF) as a suitable alternative to improve antibody treatment of patients with high-risk neuroblastoma. 2 The authors strongly advocate finding ways to increase accessibility of granulocyte-monocyte colony-stimulating factor (GM-CSF, sargramostim), used in combination with dinutuximab in North America, also in countries where this treatment is currently not available. We fully agree that all relevant stakeholders should participate in finding a permanent solution to prevent potentially suboptimal treatment of patients with high-risk neuroblastoma in the absence of sargramostim.…”
mentioning
confidence: 99%